'The People's Dinosaur': How Dippy became British Heritage. Issue 1 (April 2022) - Billing, Björn
Abstract : In 2015 the Natural History Museum (NHM) in London informed the public that their most beloved exhibit, a Diplodocus replica nicknamed Dippy, was going to be dismounted and removed from the large entrance hall. Protests arose immediately: Facebook groups appeared, the hashtag #SaveDippy was trending and petitions were sent to the authorities. Paleontogists and celebrities debated the decision in the newspapers. When three years the NHM later launched a tour project that will take Dippy around the UK, the dinosaur's popularity grew to unprecedented heights. Its significance shifted from being a London landmark to becoming a national icon. Although the original fossil was excavated in Wyoming in the late nineteenth century, Dippy has unofficially gained the status of British heritage. This article analyses this transformation by putting recent events into historical contexts, paying particular attention to the presentation of the dinosaur in the NHM in May 1905. The analysis shows how the skeleton cast was articulated with ideological intent in a confluence of museums, science, mass media, politics and popular culture. Throughout its history, Dippy has been appropriated and contested by various actors, and nationalistic ideas have been a recurrent theme in the heritageisation process.